THE IMPACT OF COVID-19 LOCKDOWN ON PARENTS’ MENTAL HEALTH - Shaymardon Norov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Parents are a crucial population vulnerable to mental health issues, especially during difficult periods, such as the COVID-19 pandemic lockdown and subsequent school closure. The attachment theory of developmental psychology posits that parents serve as external regulators of young children’s emotional states. Caring for children in difficult times requires parents to comprehend children’s emotional states, control their behaviors, and provide them with comfort and response. However, the burden of care can be overwhelming during extreme situations, and the psychosocial crisis of uncertainty, fear, and anxiety about the pandemic might worsen psychological distress in parents. Local lockdown at the end of January 2020 was adopted by the Chinese government as an integral part of its anti-COVID-19 strategy. Research has suggested that parenting daily hassles during children’s remote schooling are associated with parents’ parenting efficacy and mental health, which is consistent with the framework in developmental trauma research. Considering the widespread and serious consequences of the COVID-19 pandemic, addressing parenting daily hassles and their effects on parents’ mental health during the lockdown is necessary. The unprecedented public health crisis sheds light on the active parenting role since young children cannot care for themselves at home. Parents play a critical part in helping young children cope with negative emotional experiences brought about by the COVID-19 pandemic and social isolation. The burden of parenting may exceed parents’ thinking capacity.